Safety and efficacy of dendritic cell-based immunotherapy DCVAC/OvCa added to first-line chemotherapy (carboplatin plus paclitaxel) for epithelial ovarian cancer: a phase 2, open-label, multicenter, randomized trial. Issue 1 (6th January 2022) - Rob, Lukas; Cibula, David; Knapp, Pawel; Mallmann, Peter; Klat, Jaroslav; Minar, Lubos; Bartos, Pavel; Chovanec, Josef; Valha, Petr; Pluta, Marek; Novotny, Zdenek; Spacek, Jiri; et al.
Abstract : Background: Most patients with epithelial ovarian cancer (EOC) relapse despite primary debulking surgery and chemotherapy (CT). Autologous dendritic cell immunotherapy (DCVAC) can present tumor antigens to elicit a durable immune response. We hypothesized that adding parallel or sequential DCVAC to CT stimulates antitumor immunity and improves clinical outcomes in patients with EOC. Based on the interim results of sequential DCVAC/OvCa administration and to accommodate the increased interest in maintenance treatment in EOC, the trial was amended by adding Part 2. Methods: Patients with International Federation of Gynecology and Obstetrics stage III EOC (serous, endometrioid, or mucinous), who underwent cytoreductive surgery up to 3 weeks prior to randomization and were scheduled for first-line platinum-based CT were eligible. Patients, stratified by tumor residuum (0 or <1 cm), were randomized (1:1:1) to DCVAC/OvCa parallel to CT (Group A), DCVAC/OvCa sequential to CT (Group B), or CT alone (Group C) in Part 1, and to Groups B and C in Part 2. Autologous dendritic cells for DCVAC were differentiated from patients' CD14 + monocytes, pulsed with two allogenic OvCa cell lines (SK-OV-3, OV-90), and matured in the presence of polyinosinic:polycytidylic acid. We report the safety outcomes (safety analysis set, Parts 1 and 2 combined) along with the primary (progression-free survival (PFS)) and secondary (overall survival (OS)) efficacy endpoints. Efficacy endpoints were assessed in the modified intention-to-treat (mITT) analysis set in Part 1. Results: Between November 2013 and March 2016, 99 patients were randomized. The mITT (Part 1) comprised 31, 29, and 30 patients in Groups A, B, and C, respectively. Baseline characteristics and DCVAC/OvCa exposure were comparable across the treatment arms. DCVAC/OvCa showed a good safety profile with treatment-emergent adverse events related to DCVAC/OvCa in 2 of 34 patients (5.9%) in Group A and 2 of 53 patients (3.8%) in Group B. Median PFS was 20.3, not reached, and 21.4 months in Groups A, B, and C, respectively. The HR (95% CI) for Group A versus Group C was 0.98 (0.48 to 2.00; p=0.9483) and the HR for Group B versus Group C was 0.39 (0.16 to 0.96; p=0.0336). This was accompanied by a non-significant trend of improved OS in Groups A and B. Median OS was not reached in any group after a median follow-up of 66 months (34% of events). Conclusions: DCVAC/OvCa and leukapheresis was not associated with significant safety concerns in this trial. DCVAC/OvCa sequential to CT was associated with a statistically significant improvement in PFS in patients undergoing first-line treatment of EOC. Trial registration number: NCT02107937, EudraCT2010-021462-30.